Inverse design of a broadband silicon nitride polarization rotor - Bustamante, Yesica R.R.; Paula, Rômulo A. de [UNESP]; Aldaya, Ivan [UNESP] (My University, 2021)
In this work, we present the design for a broadband, compact and efficient silicon nitride polarization rotor. This work uses the inverse design method and the results show the polarization rotor with a footprint of 15x3 µm2